CLaSSES: a New Digital Resource for Latin Epigraphy - Irene De Felice; Giovanna Marotta; Margherita Donati (IJCoL)
CLaSSES (Corpus for Latin Sociolinguistic Studies on Epigraphic textS) is an annotated corpus aimed at (socio)linguistic research on Latin inscriptions. Provided with linguistic, extra- and meta-linguistic features, it can be used to perform quantitative and qualitative variationist analyses on Latin epigraphic texts. In particular, it allows the user to analyze spelling (and possibly phonetic-phonological) variants and to interpret them with reference to the dating, the provenance place, and the type of the texts. This paper presents the first macro-section of CLaSSES, focused on inscriptions of the archaic and early periods (CLaSSES I).